Antihypertensive Action of Allantoin in Animals. (12th March 2014) - Chen, Mei-Fen; Tsai, Jo-Ting; Chen, Li-Jen; Wu, Tung-Pi; Yang, Jia-Jang; Yin, Li-Te; Yang, Yu-lin; Chiang, Tai-An; Lu, Han-Lin; Wu, Ming-Chang
Abstract : The agonists of imidazoline I-1 receptors (I-1R) are widely used to lower blood pressure. It has been indicated that guanidinium derivatives show an ability to activate imidazoline receptors. Also, allantoin has a chemical stricture similar to guanidinium derivatives. Thus, it is of special interest to characterize the effect of allantoin on I-1R. In conscious male spontaneous hypertensive rats (SHRs), mean blood pressure (MBP) was recorded using the tail-cuff method. Furthermore, the hemodynamic analyses in catheterized rats were applied to measure the actions of allantoin in vivo. Allantoin decreased blood pressures in SHRs at 30 minutes, as the most effective time. Also, this antihypertensive action was shown in a dose-dependent manner from SHRs treated with allantoin. Moreover, in anesthetized rats, allantoin inhibited cardiac contractility and heart rate as showing in hemodynamic d P / d t max significantly. Also, the peripheral blood flow was markedly increased by allantoin. Both actions were diminished by efaroxan at the dose sufficient to block I-1R. Thus, we suggest that allantoin, as I-1R agonist, has the potential to develop as a new therapeutic agent for hypertension in the future.